Influence of Different Sweeteners on the Stability of Anthocyanins from Cornelian Cherry Juice - Bianca Moldovan; Luminita David (Foods, 2020)
Cornelian cherries are red fruits which can be considered as a valuable dietary source of antioxidant biologically active compounds, especially anthocyanins. The purpose of the present study was to investigate the anthocyanins degradation process in Cornelian cherry juice supplemented with different sweeteners. Four formulations of Cornelian cherry juice were prepared using different sugars (sucrose, fructose) or artificial sweeteners (aspartame and acesulfame potassium). The obtained juices were stored at three distinct temperatures (2 °C, 25 °C, and 75 °C) in order to evaluate the effects of the sweetener and storage conditions on the pigment stability. The rate constants (k) and the half time values (t1/2) of the degradation processes were determined. The highest stability was observed for the anthocyanins from the unsweetened juice stored at 2 °C (k = 0.5·10−3 h−1), while the most accelerated degradation was registered for the fructose sweetened juice stored at 75 °C (k = 91.65·10−3 h−1). The presence of the different sweeteners in the Cornelian cherry juice affects their pigment stability during storage. The highest change in the retention of anthocyanins was determined by the presence of fructose, while acesulfame potassium had the less deleterious effect.